2008
DOI: 10.1007/s00586-008-0691-0
|View full text |Cite
|
Sign up to set email alerts
|

The changes of relative position of the thoracic aorta after anterior or posterior instrumentation of type I Lenke curve in adolescent idiopathic thoracic scoliosis

Abstract: The risk of impingement of the aorta associated with thoracic vertebral screw or pedicle screw instrumentation in the treatment of thoracic scoliosis has been an important concern. To understand this phenomenon more systematically, the relative position of the aorta with reference to the thoracic vertebrae in right thoracic adolescent idiopathic scoliosis (AIS) following anterior and posterior spinal instrumentation was analyzed in detail quantitatively; 34 patients underwent anterior (n = 14) or posterior (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Migration of the thoracic aorta in patients with main right thoracic IS treated with posterior spinal instrumentation or anterior spinal instrumentation with pleura closure has been reported previously. (Bullmann V, et al 2006, Wang W, et al 2008 In patients treated with posterior spinal instrumentation only, no change was found on the relative position of the aorta to the vertebrae. However, these studies showed that patients who were treated with anterior curve correction with pleural closure the thoracic aorta migrated anteromedially, (Bullmann V, et al 2006, Wang W, et al 2008 which was attributed to releasing the aorta through pleural dissection and derotation of the curve.…”
Section: Pleura In Non-closurementioning
confidence: 99%
See 2 more Smart Citations
“…Migration of the thoracic aorta in patients with main right thoracic IS treated with posterior spinal instrumentation or anterior spinal instrumentation with pleura closure has been reported previously. (Bullmann V, et al 2006, Wang W, et al 2008 In patients treated with posterior spinal instrumentation only, no change was found on the relative position of the aorta to the vertebrae. However, these studies showed that patients who were treated with anterior curve correction with pleural closure the thoracic aorta migrated anteromedially, (Bullmann V, et al 2006, Wang W, et al 2008 which was attributed to releasing the aorta through pleural dissection and derotation of the curve.…”
Section: Pleura In Non-closurementioning
confidence: 99%
“…(Bullmann V, et al 2006, Wang W, et al 2008 In patients treated with posterior spinal instrumentation only, no change was found on the relative position of the aorta to the vertebrae. However, these studies showed that patients who were treated with anterior curve correction with pleural closure the thoracic aorta migrated anteromedially, (Bullmann V, et al 2006, Wang W, et al 2008 which was attributed to releasing the aorta through pleural dissection and derotation of the curve. By comparing with the study from Wang et al, (Wang W, et al 2008) the clinical data and surgical outcomes were quite similar in terms of pre-op coronal and sagittal Cobb angle, curve flexibility, curve correction rate, pre-op and post-op AVT translation (Table 8 and 9).…”
Section: Pleura In Non-closurementioning
confidence: 99%
See 1 more Smart Citation
“…1,14,17,21 In addition, some cadaveric anatomical studies on the anterior instrumentation of the thoracic and lumbar spine in adults have quantitatively evaluated the relationship between the screw placement angle and the spinal canal since the screw may penetrate the spinal canal if its angle exceeds the maximum. 3,4 To the best of our knowledge, no reports have documented the maximum posterior screw placement angle into the spinal canal in a pediatric population in order to consider age-dependent differences and other variations in ossification.…”
mentioning
confidence: 99%
“…These studies demonstrated that the aorta is always located on the left side of the thoracic spine and stays in front of the lumbar spine in normal subjects [5] while tending to reside on the lateral side of the spine in scoliotic patients, and this change may elevate the risk of the aorta impingement when placing screws on the concave side of the thoracic spine [6][7][8][9]. However, the majority of such studies have always paid attention to the relative position of the aorta to thoracic vertebrae, and there was little information concerning the relative position of the aorta to thoracolumbar or lumbar vertebrae [6][7][8][9][10]. Moreover, these studies did not include curve pattern into consideration as most studies were performed on patients with right-sided thoracic curves and did not compare the risk of the aorta impingement among different curve patterns.…”
Section: Introductionmentioning
confidence: 99%